Plantar pressure distribution in elderly subjec Ts after proprioceptive exercises - Fábio Marcon Alfieri (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n2p137 Changes related to aging limit cutaneous plantar perception, interfering in postural control. The aim of this study was to verify the effects of a regular program of proprioceptive intervention on plantar pressure distribution in older adults. Plantar pressure distribution was evaluated in 29 volunteers (63.06 ±2.84 years) standing on both feet with eyes open (EO) and eyes closed (EC). After baropodometric evaluation, the subjects attended 3 weekly proprioceptive intervention sessions of 1 hour's duration for 3 months. Results: Prior to the intervention, participants exhibited mean EO values of 0.29 ±0.044 Kg/cm² for the right foot and 0.31 ±0.04 Kg/cm² for the left foot (p=0.0078) and post-intervention these were 0.28±0.04 Kg/cm² and 0.30±0.04 Kg/cm², respectively. Pre-intervention EC values were 0.30 ±0.044 Kg/cm² for the right and 0.31 ±0.05 Kg/cm² for the left foot and post-intervention these figures were 0.28 ±0.04 Kg/cm² and 0.29 ±0.049 Kg/cm², respectively. The results of MANOVA indicated significant differences in contact pressure between pre-intervention and post-intervention measurements. Conclusions: The intervention used here reduced the participants' plantar pressure, but was unable to improve the distribution of plantar pressure between the right and left feet.